Disruption of FGF2-Heparin-FGFR1 Complex Formation by Antiangiogenic Small Molecule Found In Silico - Mahdavi, Mahdiyeh Sadat; Shokrgozar, Mohammad Ali; Sardari, Soroush; Majidi, Mohammad; Ghadam, Mona (Asian Pacific Journal of Cancer Biology, 2017)
Background: Basic fibroblast growth factor (FGF2) is one of the most potent proangiogenic proteins involving in tumor angiogenesis. Interaction of heparin with FGF2 and FGF2 receptor (FGFR1) form a ternary complex that is prerequisite for FGF2 proangiogenic activity. Therefore, this interaction can be an important target for inhibition of angiogenesis. Material and Method: In this study, we performed screening studies by computer-aided techniques to find a small molecule interfering with this interaction. Based on ionic interactions, we found seventeen small molecules which had the capability of angiogenic inhibition. According to important negative charge distances, benzene-1, 2, 4-tricarboxylic acids, known as Trimellitic acid (TMLA), was chosen. MTT viability test, real time PCR, tube formation assay, and Flowcytometry technique were used to evaluate TMLA effect. Results: Here, the viability of HUVECs was decreased following exposure to TMLA only at high concentrations. According to real time PCR, gene expression was dramatically decreased in comparison to negative control, indicating that TMLA is an effective agent on reduction of CD31 expression. At half maximal inhibitory concentration (13mM), TMLA inhibited HUVEC tube formation process. Annexin V-FITC / PI flow cytometry technique revealed that TMLA inhibitory effect was via apoptosis. Conclusion: With respect to findings of the present study, it is possible to extend FGF2 inhibitors with much specificity based on ionic interactions strategy.